ANALISIS STRATEGI MANAJEMEN OPERASIONAL PADA UMKM KULINER: STUDI KASUS AYAM PENYET RAFFA DI MEDAN - Cut Nasiva Danil; Alya Ridha Nasution; Chelsy Nainggolan; Clara Pratama; Dionisius Sihombing; Marito Ritonga (Ekonis: Jurnal Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a vital role in the Indonesian economy, yet they face challenges of competition and limited resources. This study aims to analyze operational management strategies at Ayam Penyet Raffa MSME in Medan and identify the operational problems encountered. Using a qualitative approach with a case study method, data were collected through in-depth interviews with the business owner, direct observation, and documentation. The findings revealed five main problems: a "sold out close" policy without reserve stock, lack of standardization in chili sauce measurements leading to taste inconsistency, no menu innovation for seven years, less ergonomic facility layout with the production area close to customers, and suboptimal use of social media for promotion. This study concludes that improving operational management through the implementation of SOPs, product innovation, better inventory management, facility rearrangement, and optimizing digital promotion can enhance operational efficiency and competitiveness of culinary MSMEs.Keywords— Operational Management, Culinary MSMEs, Quality Control, Facility Layout, Digital Marketing